2001
DOI: 10.1067/mhn.2001.117871
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Immune Inhibitory Cd34+ Progenitor Cells in the Peripheral Blood of Patients with Node Positive Headc and Neck Squamous Cell Carcinomas and The Ability of These CD34+ Cells to Differentiate Into Immune Stimulatory Dendritic Cells

Abstract: Differentiation of tumor-mobilized CD34+ cells into dendritic cells may be an immunotherapeutic approach to stimulate antitumor reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
(41 reference statements)
0
34
0
Order By: Relevance
“…However, knowledge of MDSC is primarily based on preclinical work, and to date only few published studies have involved cancer patients [1,11,19,23,30]. Considering the importance of MDSC as an important mechanism of cancer immune-evasion, more definitive human studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowledge of MDSC is primarily based on preclinical work, and to date only few published studies have involved cancer patients [1,11,19,23,30]. Considering the importance of MDSC as an important mechanism of cancer immune-evasion, more definitive human studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently few published studies to date have investigated the clinical significance of MDSC [1,11,19,23,30]. To date the most comprehensive work in cancer patients established that MDSC were double negative for the MHC class II molecule (HLA DR) and any other surface markers of mature lymphoid or myeloid cells (CD3, CD19, CD57, CD14) or Lin −/Lo [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that G-CSF receptor signaling enhances the invasiveness of human HNSCC cells in vitro (24). Additionally, GM-CSF induces immunosuppressive CD34 + progenitor cells that interfere in host antitumor competence (34), thereby contributing to the decreased immune responsiveness in HNSCC-bearing mice (35). Accordingly, the expression of vascular endothelial growth factor (VEGF) and platelet-derived growth factor-AB together with G-CSF and/or GM-CSF expression correlated with a significantly poorer patient prognosis in HNSCC (23).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, expression of G-CSF and GM-CSF by tumor cells is associated with a coexpression of the respective receptors, and there are first indications that this factorreceptor coexpression may lead to an autocrine stimulation of tumor cell growth, migration, invasion, and metastasis: e.g., G-CSF and GM-CSF stimulate proliferation and migration of SCCs of the skin and gliomas (5,11,12); GM-CSF enhances proliferation in renal cell carcinoma (23); expression of G-CSF is associated with more aggressive tumor growth in cervical cancer (24) and enhanced invasion and metastasis in head and neck tumors (9,25). 1 In addition to this autocrine effect on the cytokine-producing tumor itself, G-CSF and GM-CSF may also act in a paracrine manner on the tumor-surrounding stroma, e.g., by promoting an angiogenic response (14,15,26,27). Furthermore, constitutive expression of G-CSF has been shown to be associated with leukocytosis (16 -19) and better neutrophil survival (22).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, constitutive expression of G-CSF has been shown to be associated with leukocytosis (16 -19) and better neutrophil survival (22). Expression of GM-CSF in SCCs of the head and neck stimulates the recruitment of CD34ϩ cells, resulting in host immune suppression (27). Interestingly, the recruitment of inflammatory cells to the tumor vicinity has been implicated in the potentiation of neoplastic progression via the production of paracrine factors and could therefore have a strong impact on tumor progression (28).…”
Section: Introductionmentioning
confidence: 99%